2001
DOI: 10.1002/1521-396x(200112)188:4<1577::aid-pssa1577>3.0.co;2-j
|View full text |Cite
|
Sign up to set email alerts
|

Reflection Anisotropic Spectroscopy as a Tool in the Fabrication of Liquid Crystal Devices

Abstract: We demonstrate the potential of Reflection Anisotropic Spectroscopy (RAS) as a new tool for predicting optical microelectronic device characteristics prior to assembly. The Reflection Anisotropy (RA) of polymer alignment layers has been studied as a function of rubbing. This data contains information about the suitability of the surface as an alignment layer as well as film thickness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
1

Year Published

2002
2002
2004
2004

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 6 publications
0
10
1
Order By: Relevance
“…Further rubbing leads to a small reduction in measured anisotropy, consistent with the onset of surface damage observed by AFM. This is in contrast to our previous studies of rubbed nylon 6-6 14 in which we found the RAS signal to collapse completely after only two rubs, as shown by the triangular data points of Fig. 3͑c͒.…”
Section: Resultscontrasting
confidence: 99%
“…Further rubbing leads to a small reduction in measured anisotropy, consistent with the onset of surface damage observed by AFM. This is in contrast to our previous studies of rubbed nylon 6-6 14 in which we found the RAS signal to collapse completely after only two rubs, as shown by the triangular data points of Fig. 3͑c͒.…”
Section: Resultscontrasting
confidence: 99%
“…These examples are drawn from a field to which RAS has only very recently been applied, 9,10 namely the construction of liquid crystal displays. Such devices function by the alignment of liquid crystal molecules at surfaces due to some kind of anisotropic surface modification.…”
Section: Resultsmentioning
confidence: 99%
“…Here we have studied 1 cm square glass substrates coated with a thin indium tin oxide electrode layer followed by a ϳ0.3-m-thick polyimide layer, as used to produce miniature displays and described elsewhere. 9 An atomic force microscopy ͑AFM͒ image of a typical sample after passing under a rotating velvet drum is shown in Fig. 3͑a͒ and clearly shows rub-induced grooves with a depth of ϳ30 nm.…”
Section: A Examplementioning
confidence: 99%
See 1 more Smart Citation
“…Mechanical rubbing of a PI film will also result in changes to the physical properties of the film, especially the surface morphology and it has been reported that anchoring energies change with rubbing strength [7]. The examination of rubbed PI films by means of reflection anisotropy spectroscopy (RAS) [8] and reflection ellipsometry [9,10] reveals that mechanical rubbing generates surface anisotropy. These changes in the molecular alignment and surface topography of the alignment layer affect the molecular alignment of the ferroelectric liquid crystal (FLC) layer as it is in direct contact with the PI film.…”
Section: Introductionmentioning
confidence: 99%